The Fourth International Conference on Dense Z-Pinches 1997
DOI: 10.1063/1.53818
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hohlraum experiments on SATURN

Abstract: Ab s t ra c tWe hiwe imploded a 17.5 mm diameter 120-tungsten-wire a m y weighing 150 U g h n onto a 1 mrn diameter silicon aerogel foam weighing 650 pgfcm, using the pulsed p o u a driver SATURV. . 4 p& current of 7.0 M-4 drives a 18 N impiosiou to strike time followed by S N cf foam compression until stagmtion. Thc tungsten strikcs the foam ivitti n 50 crn'us implosion veIocity. Radiation tempcnrures \sere measwcd from thc sidc nnci nfong the nsis with fiItered x-ray diode arrays. There is evidence of ndinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For instance, this ratio is about 0.78 on the Z experiments, 11,13 and about 0.69 on the Saturn experiments. 15 This kind of loads can provide a more efficient energy conversion from the wire-array plasma to the converter in order to generate a higher radiation temperature hohlraum. It is found that the collision of the wire-array plasma with the converter just takes place several to 10 ns earlier than the final stagnation in these cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this ratio is about 0.78 on the Z experiments, 11,13 and about 0.69 on the Saturn experiments. 15 This kind of loads can provide a more efficient energy conversion from the wire-array plasma to the converter in order to generate a higher radiation temperature hohlraum. It is found that the collision of the wire-array plasma with the converter just takes place several to 10 ns earlier than the final stagnation in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Several other machines, such as the Angara-5-1 and Saturn facilities, also conducted dynamic hohlraum or double liner experiments. 2,14,15 Based on the results on these three generators, Nash presented an approximate scaling of dynamic hohlraum radiation temperature as T ¼ 56I 0:46 eV, 9 where I is the peak drive current in MA. A straightforward extrapolation to a machine of about 60 MA was then suggested to explore the physics of high yield fusions using dynamic hohlraums.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In these experiments, SATURN drives lowdensity Si aerogel ͑SiO 2 ͒ and agar ͑C 7 H 13 NO 5 ͒ foam loads with currents of about 7 MA with a rise time of approximately 50 ns. The purpose of the experiments is to study the initiation, acceleration, and stagnation phases of the pinch.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation temperatures required for ignition of an indirect-drive DT capsule are in the range of 250 eV for designs similar to ICF capsules driven by lasers (Lindl, 1995) The temperatures presently reached in the Z-pinch experiments are in the range of 130-160 eV (e.g., Nash et al, 1997b). These ICF ignition and high yield capsules also require precise pulse shaping and a high degree of radiation symmetry.…”
Section: B2mentioning
confidence: 99%